Case Report: DOCK8 Deficiency Without Hyper-IgE in a Child With a Large Deletion - Venegas-Montoya, Edna; Staines-Boone, Aidé Tamara; Sánchez-Sánchez, Luz María; García-Campos, Jorge Alberto; Córdova-Gurrola, Rubén Antonio; Salazar-Galvez, Yuridia; Múzquiz-Zermeño, David; González-Serrano, María Edith; Lugo Reyes, Saul O. (Frontiers in Pediatrics, 2021)
Autosomal recessive (AR) DOCK8 deficiency is a well-known actinopathy, a combined primary immune deficiency with impaired actin polymerization that results in altered cell mobility and immune synapse. DOCK8 deficient patients present early in life with eczema, viral cutaneous infections, chronic mucocutaneous candidiasis, bacterial pneumonia, and abscesses, together with eosinophilia, thrombocytosis, lymphopenia, and variable dysgammaglobulinemia that usually includes hyper-IgE. In fact, before its genetic etiology was known, patients were described as having a form of Hyper-IgE syndrome, a name now deprecated in favor of genetic defects. We describe a school-age male patient with a clinical picture suggestive of DOCK8 deficiency, except for high serum IgE or a family history: early onset, failure to thrive, eczema, warts, condyloma, bronchiolitis, pneumonia, recurrent otitis media, bronchiectasis, candidiasis, leukocytosis, eosinophilia, high IgA, low IgG and low CD4+ T cells. We were able to confirm the diagnosis through protein expression and whole-exome sequencing. We review the clinical, laboratory and genetic features of 200 DOCK8 deficient patients; at least four other patients have had no elevated IgE, and about forty percent do not have hyper-IgE (above 1,000 IU/ml). Despite this, the constellation of signs, symptoms and findings allow the suspicion of DOCK8 deficiency and other actinopathies.